Simplification of Signal Flow Graphs - Prasad, V. C. (2011)
Star-delta transformations are popular in electrical engineering. Of late they have also been tried in reliability analysis. Techniques are presented here to transform a star (delta) to a delta (star) in a signal flow graph. This allows us to simplify some non-series-parallel graphs using a series parallel framework. Unlike the case of electrical circuits, these transformations are not always possible. It is shown that a star-to-delta transformation is always possible. But a delta can be transformed into a star if and only if a certain loop condition is satisfied. An important advantage of these techniques is that they can be used even when there are directed loops, whereas this is not the case with standard series parallel techniques.